2017
DOI: 10.1159/000485323
|View full text |Cite
|
Sign up to set email alerts
|

Optical Coherence Tomography Angiography in Healthy Subjects and Diabetic Patients

Abstract: Fluorescein angiography and indocyanine green angiography provide information about the normal retinal and choroidal vascular perfusion. They allow the evaluation of different diseases and increase the capability to define and diagnose several pathological conditions. Fluorescein angio graphy is the “gold standard” in imaging the retinal vascular bed and its changes, although not all the different layers of the capillary network can be visualized in a bidimensional examination. Optical coherence tomography ang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 26 publications
1
24
0
2
Order By: Relevance
“…13,20,21 The results herein agree with these findings (Table). Furthermore, compared to FA, OCTA can also visualize periarterial capillary-free zones [16][17][18] and vessel connections at the level of precapillary arterioles and venules. These advantages enabled us to identify and trace small branches of arteries and veins on OCTA images.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…13,20,21 The results herein agree with these findings (Table). Furthermore, compared to FA, OCTA can also visualize periarterial capillary-free zones [16][17][18] and vessel connections at the level of precapillary arterioles and venules. These advantages enabled us to identify and trace small branches of arteries and veins on OCTA images.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned previously, OCTA visualizes a narrow capillary-free zone that physiologically exists around retinal arteries. [16][17][18] Automated quantification could erroneously detect this physiologic zone as a nonperfusion area, and the A/V ratio could have been overestimated because the periarterial physiologic capillary-free zones could still contribute to nonperfusion areas when combined with actual areas of nonperfusion in eyes with DR. However, we confirmed manually that this physiologic capillary-free zone was not detected as areas of nonperfusion by our software in eyes without DR. 13 Moreover, a very recent study quantitatively demonstrated that the periarterial capillary-free zone in severe NPDR was enlarged compared to that in the normal subjects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The choriocapillaris becomes wider and longer towards the equatorial region. In contrast to other capillary networks throughout the human body, the luminal diameter of these capillaries is significantly larger (approximately 20 μm at the macula and 18-50 μm at the periphery) [14]. Macula involves high density of photoreceptors, that results in a high metabolic demand at this region which is supplied primarily by choroid.…”
Section: Introductionmentioning
confidence: 99%
“…Recent literature has highlighted the importance of changes in choroidal blood flow in patients with diabetic retinopathy. [6][7][8] Therefore, a comprehensive evaluation of OCTA imaging in DR should consider the choroid in addition to the retina.…”
Section: Introductionmentioning
confidence: 99%